2021
DOI: 10.1200/jco.20.02608
|View full text |Cite|
|
Sign up to set email alerts
|

Third-Party BK Virus-Specific Cytotoxic T Lymphocyte Therapy for Hemorrhagic Cystitis Following Allotransplantation

Abstract: PURPOSE BK virus-associated hemorrhagic cystitis (BKV-HC) is a common complication of allogenic hematopoietic stem cell transplantation (AHSCT), particularly in recipients of alternative donor transplants, which are being performed in increasing numbers. BKV-HC typically results in painful hematuria, urinary obstruction, and renal dysfunction, without a definitive therapeutic option. METHODS We performed a clinical trial (ClinicalTrials.gov identifier: NCT02479698 ) to assess the feasibility, safety, and effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 28 publications
2
29
0
Order By: Relevance
“…The effector phenotype predicts the capacity to mediate early viral clearance, whereas CM T cells persist and provide long-term immunity after adoptive transfer (Powell et al, 2005). Indeed, our group and others have confirmed that adoptive infusion of VSTs with a predominantly CD4+ EM phenotype results in successful eradication of severe viral infections such as JCV, BKV, and adenovirus (Heslop et al, 2010;Leen et al, 2010;Muftuoglu et al, 2018;Olson et al, 2021). We also investigated the functional state of SARS-CoV-2 T cells based on their ability to produce one or more cytokines in response to ex vivo stimulation with SARS-CoV-2 Cell Reports 36, 109432, July 20, 2021 7 Article ll OPEN ACCESS antigens.…”
Section: Discussionmentioning
confidence: 60%
“…The effector phenotype predicts the capacity to mediate early viral clearance, whereas CM T cells persist and provide long-term immunity after adoptive transfer (Powell et al, 2005). Indeed, our group and others have confirmed that adoptive infusion of VSTs with a predominantly CD4+ EM phenotype results in successful eradication of severe viral infections such as JCV, BKV, and adenovirus (Heslop et al, 2010;Leen et al, 2010;Muftuoglu et al, 2018;Olson et al, 2021). We also investigated the functional state of SARS-CoV-2 T cells based on their ability to produce one or more cytokines in response to ex vivo stimulation with SARS-CoV-2 Cell Reports 36, 109432, July 20, 2021 7 Article ll OPEN ACCESS antigens.…”
Section: Discussionmentioning
confidence: 60%
“…Recently, thirdparty pathogen-specific cytotoxic T cells have been developed for off-the-shelf use. Olsen et al reported a trial using third-party BK virus-specific cytotoxic T cell infusions into 59 patients developing BK virus-associated hemorrhagic cystitis after allo-HCT, and a day 14 overall response rate of 67.7% was observed (69). Moreover, several techniques are being investigated for optimal T cell allodepletion with preservation of pathogenspecific responses and Tregs (70).…”
Section: Prophylactic DLImentioning
confidence: 99%
“…Using HSCT-donor derived VSTs, Nelson et al found that 87% of patients with BK viremia and/or HC (n=38) responded to ≥1 anti-BK VST infusions; 58% completely cleared BKV and demonstrated resolution of HC symptoms ≤ grade II (10). Olson et al describe comparable outcomes with HLA-matched third-party anti-BK VSTs (21). Infusion-related adverse events were rare with HSCT-donor derived or third-party VSTs (10,21).…”
Section: Discussionmentioning
confidence: 98%
“…Olson et al describe comparable outcomes with HLA-matched third-party anti-BK VSTs (21). Infusion-related adverse events were rare with HSCT-donor derived or third-party VSTs (10,21).…”
Section: Discussionmentioning
confidence: 98%